Standardization of the procedural load of the Judicial Branch of the Republic of Peru: A structured factorial approach - Huamachumo de la Cuba, Luis E. (2005)
This study examined the extent to which technology and human resources in each court can explain standards of Pending Causes and Judicial Production. The discussion draws attention to the summary variables on both location and organizational system from the 2003 Judicial Power's General Bureau Statistical Yearbook. In this context, the Structured Factorial MANOVA was applied to test our hypothesis over the Civil, Labour, and Family court.